Kepuasan Masyarakat terhadap Kualitas Pelayananan Publik berbasis Digital di Desa Citemu Kecamatan Mundu Kabupaten Cirebon - Askarno, Askarno; Anwar, Syahrul; Nurwahid, Arulfalah; Anisa, Mahdania; Toto, Toto (Blantika: Multidisciplinary Journal, 2025)
The main purpose of this study is to analyze the extent to which village websites can increase information disclosure, increase community participation in village development, and increase community satisfaction with the services provided by the village government. This study uses a descriptive qualitative method to obtain an overview of the effectiveness of village websites in disseminating development information and the level of community satisfaction with digital services. Data was collected through a questionnaire that included closed-ended and open-ended questions, with respondents consisting of the community as service users and village officials as providers. The results showed that most people expressed "Agree" (46%) and "Neutral" (37%) for village digital services, indicating that these services are useful but not optimal. The main factors that affect public satisfaction are service accessibility, information quality, and lack of socialization and digital education. The problem of limited internet networks and low digital literacy is a challenge in the implementation of digital services. Therefore, it is necessary to improve technology infrastructure and sustainable educational programs so that the public can better understand and utilize digital services effectively